2019
DOI: 10.1039/c9sc03894a
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium-catalyzed asymmetric intramolecular hydroarylation of allenes: access to functionalized benzocycles

Abstract: A rhodium-catalyzed regio- and enantioselective cyclization of tethered allenylbenzenes is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 34 publications
(2 reference statements)
0
12
0
Order By: Relevance
“…In 2018 and 2019, the asymmetric addition of alkyl and aryl groups to the C(sp 2 )‐C(sp) bonds of allenes 31 and 34 to form chiral C(sp 3 )‐C(sp 3 )/C(sp 2 ) bonds has been achieved by Breit and co‐workers (Scheme 17). [41,42] These two rhodium‐catalyzed asymmetric addition reaction systems were completed by using Josiphos L3 and L4 as chiral control ligands, respectively. The experimental results showed that various aliphatic allenes 31 reacted smoothly with malonitrile 32 using Josiphos L3 as chiral control ligand to provide products 33 in 44–99 % yields with 89 : 11‐95 : 5 er [41] .…”
Section: Asymmetric Addition To C(sp2)‐c(sp) Bonds Of Allenesmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2018 and 2019, the asymmetric addition of alkyl and aryl groups to the C(sp 2 )‐C(sp) bonds of allenes 31 and 34 to form chiral C(sp 3 )‐C(sp 3 )/C(sp 2 ) bonds has been achieved by Breit and co‐workers (Scheme 17). [41,42] These two rhodium‐catalyzed asymmetric addition reaction systems were completed by using Josiphos L3 and L4 as chiral control ligands, respectively. The experimental results showed that various aliphatic allenes 31 reacted smoothly with malonitrile 32 using Josiphos L3 as chiral control ligand to provide products 33 in 44–99 % yields with 89 : 11‐95 : 5 er [41] .…”
Section: Asymmetric Addition To C(sp2)‐c(sp) Bonds Of Allenesmentioning
confidence: 99%
“…Branched cycloaliphatic allenes have also been shown to be suitable reaction partners, even though their reactions were carried out with slightly lower enantioselectivities (85 : 15‐90.5 : 9.5 er) [41] . Employing Josiphos L4 ligand, the rhodium‐catalyzed intramolecular addition of electron‐rich benzenes to allenes 34 afforded α‐chiral benzocycles 35 in 60–99 % yields with 83–99 % ee [42] . It was worth noting that regardless of whether the benzene ring contained two or three alkoxy (siloxy) groups, the substrates exhibited good tolerance to this catalytic system.…”
Section: Asymmetric Addition To C(sp2)‐c(sp) Bonds Of Allenesmentioning
confidence: 99%
“…The hydrofunctionalization of allenes through the generation of metal allyl complexes has become an emerging atom-economical technology for the construction of allylic stereocenters. Mechanistically, we proposed that Rh­(I) oxidative addition to a Brønsted acid would generate a Rh­(III)-H (Figure b). After insertion of allene 44 and formation of the Rh allyl complex 45 , allylic substitution with Hantzsch ester 46 generates product 43 and pyridinium 47 .…”
Section: Tandem Catalysismentioning
confidence: 99%
“…Transformations related to method a employ various metals as efficient promoters from perhaps less common Bi(III) or Hg(II) to typically used Au(I), Rh(II), Pt(II), or Pd(0) [4]. Some of these reactions do not proceed via initial activation of CH bond but rather via activation of the allene functionality making it susceptible to the nucleophilic attack by various activated aromatic rings formally producing hydroarylated products.…”
Section: Introductionmentioning
confidence: 99%